2003
DOI: 10.1159/000075553
|View full text |Cite
|
Sign up to set email alerts
|

Serum Progastrin and Its Products, Gastric Acid Secretion and Serum Pepsinogen I in Gastric Cancer

Abstract: Background: Numerous studies have shown an association between Helicobacter pylori (Hp) infection and gastric cancer (GC). Study: This study was designed to determine the role of cytotoxin-associated gene A (CagA)-positive Hp infection, serum amidated gastrins and their precursor, progastrin, gastric acidity and serum pepsinogen I (PG-I) levels in gastric cancerogenesis in 74 cancer patients and in 77 age- and gender-matched controls. Serum IgG antibodies to Hp and CagA and levels of IL-8 and PG-I were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…This increased risk has also been illustrated in animal models of gastric inhibition [96]. The mechanism for this is believed to be increased gastrin secretion in response to acid inhibition.…”
Section: Controversies In Acid Suppressionmentioning
confidence: 95%
“…This increased risk has also been illustrated in animal models of gastric inhibition [96]. The mechanism for this is believed to be increased gastrin secretion in response to acid inhibition.…”
Section: Controversies In Acid Suppressionmentioning
confidence: 95%
“…Furthermore, in gastric cancer patients the stomach is not highly acidic, which is not the case in peptic ulcer patients. 22,23 In a study of European and American patients, the primary disease in stomal ulcer was duodenal ulcer in 95% of cases, gastric ulcer in 3%, and gastroduodenal ulcer in 2%; 24 in Japan the primary disease was duodenal ulcer in 65.9% of cases, gastric ulcer in 19.1%, and gastroduodenal ulcer in 15%. 25 These fi ndings show that, preoperatively, duodenal ulcer is very frequently the primary disease in stomal ulcer, and that gastric cancer is relatively rare.…”
Section: Stomal Ulcermentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26] The involvement of the hepatic branch of the vagus nerve and the hepatic branch which connects with the celiac branch are strongly associated with the development of gallstones, as is delayed gastric evacuation due to the decreased movement of the residual stomach after a gastrectomy. 27 Factors other than a vagotomy that affect gallbladder movement include changes in the secretions of gut hormones, including cholecystokinin (CCK); edema due to surgery; decreased sensitivity of CCK receptors in the gallbladder wall due to disorders of circulation; changes in endogenous opioids in the gallbladder wall; and the length of the postoperative fasting period.…”
Section: Postoperative Cholelithiasismentioning
confidence: 99%
“…Thus, stimulation with exogenous CCK has been proven useful in diagnostic tests of gallbladder and pancreatic diseases (Rehfeld, 2004). In another way, Konturek et al (2003a) concluded by suggesting that determination of high serum progastrin, amidated gastrins and IL-8 combined with low serum pepsinogen I may be useful biomarkers of gastric cancer (often associated with an H. pylori infection) with acute pangastritis followed by chronic active gastritis, gastric atrophy, intestinal metaplasia and displasia. In addition to standard markers such as pepsinogen, gastrin and IL-8, reactive oxygen species were recently confirmed as biomarkers in patients with gastric inflammation (Naito et al 2005).…”
Section: Molecular Forms: Roles and Therapymentioning
confidence: 99%